2015
DOI: 10.1371/journal.pone.0130343
|View full text |Cite
|
Sign up to set email alerts
|

Tetraarsenictetrasulfide and Arsenic Trioxide Exert Synergistic Effects on Induction of Apoptosis and Differentiation in Acute Promyelocytic Leukemia Cells

Abstract: Since arsenic trioxide (As3+) has been successfully used in the treatment of acute promyelocytic leukemia (APL), its adverse effects on patients have been problematic and required a solution. Considering the good therapeutic potency and low toxicity of tetraarsenictetrasulfide (As4S4) in the treatment of APL, we investigated the effects of combining As4S4 and As3+ on the apoptosis and differentiation of NB4 and primary APL cells. As4S4, acting similarly to As3+, arrested the G1/S transition, induced the accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…The definitive molecular mechanism was inducing proliferation/apoptosis‐related differential protein expression profile in NB4 cells (Liu et al, ; Qi et al, ; Wang et al, ). As 4 S 4 also arrested NB4 cell growth in the G2/M phase (Lu et al, ; Wang, Zhou, Ouyang, Geng, & Wang, ). To our knowledge, the role of As 4 S 4 in enhancing apoptosis in immune cells has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…The definitive molecular mechanism was inducing proliferation/apoptosis‐related differential protein expression profile in NB4 cells (Liu et al, ; Qi et al, ; Wang et al, ). As 4 S 4 also arrested NB4 cell growth in the G2/M phase (Lu et al, ; Wang, Zhou, Ouyang, Geng, & Wang, ). To our knowledge, the role of As 4 S 4 in enhancing apoptosis in immune cells has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is triggered by two pathways; one is the death receptor-mediated extrinsic pathway, and the other is the mitochondrial-dependent intrinsic pathway (17,18). Bcl-2 family members are key components of the mitochondrial-dependent intrinsic apoptosis pathway (19). Bcl-2 family members are classified into three subgroups: The pro-apoptotic proteins, including Bax and Bak; the anti-apoptotic proteins, including Bcl-2, myeloid cell leukemia-1 and Bcl-extra large; and the BH3-only proteins, including BH3 interacting domain death agonist, p53 upregulated modulator of apoptosis and Noxa (20).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the toxicity of arsenic, arsenic trioxide has been used in a number of traditional Chinese medicines, and has been used to treat cancer ( 13 ). Previous studies have identified that ATO induces apoptosis in acute promyelocytic leukemia (APL) cells ( 14 , 15 ), glioblastoma cells ( 16 ) and gastric cancer cells ( 17 ), and inhibits cell growth in breast cancer ( 18 ). The use of ATO is also being evaluated for the treatment of certain malignancies, including lung cancer ( 19 ), hepatocellular cancer ( 20 ) and basal cell cancer ( 21 ).…”
Section: Introductionmentioning
confidence: 99%